Sabāhi’s Techniques of Depicting Semantic and Inspirational Functions and Intentions of Verses from Qur’an - Maryam Baghi (مطالعات زبانی و بلاغی)
A remarkable part of Persian literary heritage consists of the Qur’anic allusions and themes which are essential elements of rhetoric and poetics. Undoubtedly, the perception of the above-mentioned allusions and indications in the poetry of literary figures adds to the grandeur of their diction and doubles the pleasure of discerning this beauty. The present analytical-descriptive research introduces and explores the depiction of semantic and inspirational functions and intentions of Qur’anic verses in the poetry of Sabāhi Bidgoli, one of the most well-known figures in the period of Literary Return. The methods of depiction, referred to in the books of rhetoric and employed in the poetry of Sabāhi, are reviewed within 3 parts: direct usage (verbal, conceptual, and bilateral), changing the verse application, and allusive usage. This article has dealt with the poet’s approaches to undertaking those methods. The main research question is that, in addition to making use of common and known methods of receiving influence from the Qur’an, what less recognized techniques has Sabāhi taken into consideration? What are the semantic functions and intentions related to those techniques in his poetry? The research results show that, in addition to conventional methods such as adaptation, quotation, translation, and conceptual usage for emphasis and confirmation, and rhetorical functions; Sabāhi has also dealt with some lesser-known techniques among poets including: A) changing the verse application in a descriptive and discriminative approach, aiming to highlight the subject and theme; B) allusive usage for comparison or statement of preference. In the first technique, the main subject of the verse is in contrast with the subject intended by the poet. Sabāhi makes use of this technique for highlighting and defamiliarizing the subject in his poetry. In the second technique, by associating everyday natural and lyrical phenomena and subjects as well as religious characters and the Qur’anic events, the poet attempts to introduce the aforementioned themes in line with the allusions and stories in the Qur’an. Among the methods used in the poetry of Sabāhi, the allusive method with the approach of comparison and preference has the highest frequency.